RESEARCH ON THE FINANCIAL TRANSPARENCY INTO THE HEALTH PUBLIC SYSTEM IN ROMANIA. CASE OF HOSPITALS SUBORDINATED TO THE HEALTH MINISTRY - ȘTEFĂNESCU, Aurealia; ȚURLEA, Eugeniu (Annales Universitatis Apulensis Series Oeconomica, 2014)
The complexity of the public hospital activity, generated by the high resource consumption, high number of actors involved into the medical act, technological innovation, heterogenous healthcare services offered, typology of hospitals, diversity of financing sources and suppliers of financial resources as potential patients, demands a high degree of financial transparency. In this context, by the qualitative research performed, we identify the degree of financial transparency at the level of public hospitals subordinated to the Health  Ministry from Romania. This study takes into consideration a synthesis of the ideas published on this theme into the professional literature, as well as of the regulations issued by the national and international accounting regulators, by accounting entities. The results of the research pointed out that the financial transparency promoted by hospitals through the agency of official web sites is low. For most of hospitals the financial transparency is limited to the publication of revenue and expenditure budget. Only three hospitals display the completed financial statements and a reduced number of hospitals limits financial transparency at the individual level of the budgetary execution account, ballance sheet and patrimony outcome account. Also, we observe that in geographical terms, there are no significant differences regarding the hospital financial transparency. In respect of the temporal view, the published financial information is heterogenous both at individual level and global level, fact diminishing the comparison in time and space. The difficulty of investigating financial transparency of hospitals is increased by the difficulty of identifying the official sites of hospitals when lacking a database at the level of Health Ministry.